Penggunaan Bungkil Inti Sawit dalam Pakan Ayam dan Pengaruhnya pada Kualitas Pelet dan Performa Broiler: Utilization of Palm Kernel Meal in Feed and its Effect on Pellet Quality and Broiler Performance - setiana, ina; Nahrowi, N; Sumiati, S; Subekti, S (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
This study was conducted to determine the effect of inclusion Palm Kernel Meal (PKM) at the level of 0%, 5%, 10%, and 15% on the pellet quality, broiler performance including body weight (BW), average daily gain (ADG), feed intake (FI), feed conversion ratio (FCR), performance index, proportion of carcass, gizzard, liver and abdominal fat. A closed house cage held 320 broiler chickens of ROSS 308 strain. This study used a completely randomized design of 4 treatments with different PKM levels, namely P0 0%, P1 5%, P2 10%, and P3 15%. Each treatment consisted of 8 replicates, and each replicate consisted of 10 chickens. The results showed that the inclusion of PKM which increased, was inversely proportional to the quality of pellets, which decreased. Observations in the in vivo test showed that 15% PKM inclusion could increase feed consumption and body weight but decrease feed efficiency. It can be concluded, PKM inclusion at the level of 15% can increase palatability and body weight, and did not affect the percentage of carcass and gizzard, but can reduce the percentage of abdominal fat and increase the proportion of liver.